2011
DOI: 10.4049/jimmunol.1003506
|View full text |Cite
|
Sign up to set email alerts
|

Two Sorting Motifs, a Ubiquitination Motif and a Tyrosine Motif, Are Involved in HIV-1 and Simian Immunodeficiency Virus Nef-Mediated Receptor Endocytosis

Abstract: HIV-1 and SIV Nef proteins downregulate cell surface CD4 and MHC class I (MHC-I) molecules of infected cells, which are necessary for efficient viral replication and pathogenicity. We previously reported that K144 in HIV-1 Nef is di-ubiquitinated, and K144R substitution impairs Nef-mediated CD4 downregulation. In this report, we extend the role of ubiquitination at this lysine residue from Nef-mediated CD4 downregulation to Nef-mediated MHC-I downregulation and from HIV Nef to SIV Nef. All HIV-1 Nef mutants th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 60 publications
(72 reference statements)
0
10
0
Order By: Relevance
“…Further, it is reported that K144 in HIV-1 Nef is di-ubiquitinated for downregulation of CD4 and MHC-I (Cai et al, 2011). However, little is known as to whether Nef indeed plays an essential role in regulating the stability of HIV-1 viral and cellular proteins and consequent HIV-1 replication and survival of HIV-infected cells, and if so, how and to what degree Nef orchestrates overall HIV-1 and host cell protein fates during pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Further, it is reported that K144 in HIV-1 Nef is di-ubiquitinated for downregulation of CD4 and MHC-I (Cai et al, 2011). However, little is known as to whether Nef indeed plays an essential role in regulating the stability of HIV-1 viral and cellular proteins and consequent HIV-1 replication and survival of HIV-infected cells, and if so, how and to what degree Nef orchestrates overall HIV-1 and host cell protein fates during pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Immunoblotting was performed as described previously. 18 HIV-1 Nef was blotted with anti-HIV-1 Nef rabbit serum (1:10,000) (NIH). AP1 and AP2 were blotted with anti-AP1 (c) and anti-AP2 (a) mAb (1: 500).…”
Section: Immunoblottingmentioning
confidence: 99%
“…Abrogation of CD4 downregulation by mutations in the hydrophobic region is due to impairment of the Nef-AP2 interaction It is well documented that Nef-mediated CD4 downregulation is AP2 dependent. 4,[10][11][12][13][14][15][16][17][18] To confirm that the above mutations that impaired the CD4 downregulation abrogate the Nef-AP2 interaction, we analyzed the Nef- The results indicated that the M 168 S 169 /KK mutation impaired the Nef-AP2 interaction but not the Nef-AP1 interaction. The Nef-AP1 interaction is known not to be required in Nef-mediated CD4 downregulation.…”
Section: The Hydrophobic Region Downstream Of the Dileucine Motif (L mentioning
confidence: 99%
See 1 more Smart Citation
“…Both pathways are dependent on Nef 's N-terminal myristoylation site to assemble within lipid rafts in the plasma membrane. It appears that the "signalling mode" for MHC modulation is utilized in response to acute infection over the first 48 hours that specifically targets the 'mature' MHC-I proteins that are present at the cell surface [8], while the stoichiometric mode is a distinct mechanism utilized by the virus after day 3 of infection and blocks the transport of newly synthesized MHC-I proteins from the ER to the cell surface [8,[47][48][49]. In this way the HIV-1 virus can effectively block immune recognition of virus infected cells by antigen-specific CD8 + CTLs.…”
Section: Mhc Class I Downregulation By Nef Occurs By Two Different Pamentioning
confidence: 99%